2007
DOI: 10.2754/avb200776030357
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Essential Oil Intake on Changes of Plasma Antioxidant Status in Mice

Abstract: Faix Š., Š. Juhas, Z. Faixová: The Effect of Essential Oil Intake on Changes of Plasma Antioxidant Status in Mice. Acta Vet. Brno 2007, 76: 357-361.The aim of this study was to determine the effects of four essential oils intake by feed, namely Origanum vulgare, Thymus vulgaris, Cinnamomum zeylanicum Ness, and Syzygium aromaticum on antioxidant status in mice in vivo. Essential oils were in the aether oleum form. They were diluted with ethanol absolute mixed with ground pelett (0.1, 0.25, 0.57 and 1% concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
2
8
1
Order By: Relevance
“…Thyme contain Rosmarinic acid which acts as an inhibitor that inhibition syntheis of Eosinphils, this result agree with [28].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Thyme contain Rosmarinic acid which acts as an inhibitor that inhibition syntheis of Eosinphils, this result agree with [28].…”
Section: Resultssupporting
confidence: 81%
“…And disagree of the present study with [28] when they found that high dose of origanum vulgare oil had adverse effects on metabolism of mice on the contrary to the lower concentration which have appositive effects on antioxidant status. ct of phenol in olive (200 mg/kg) effect on twenty rats for 30 days, the result increase in count of lymphocytes and monocyte, the exposure to phenol component leading to inflammation , and this reaction characterized by movement of lymphocytes and monocytes from blood to the extravascular tissue this led to increase in count of lymphocytes and monocytes, Therefore, monocytes increased in circulation and phagocytosis increased in tissue, to prevent extensive damage to the body and disagree with [26] The decreases in the lymphocytes by thyme affect the effector cells of the immune system due to inhibit the body's immunity.…”
Section: Resultscontrasting
confidence: 45%
“…SOD and CAT were not significantly affected in chickens fed diet supplemented with Cinnamomum zeylanicum essential oil. It was observed that feeding diets containing different doses of essential oils affected the GPx activity in the blood of mice (Faix et al 2007). Differences in antioxidant activities of cinnamon might arise from different parts of plant.…”
Section: Discussionmentioning
confidence: 98%
“…Measurements of plasma antioxidants intended to assess the total antioxidant status in vivo showed higher values in broilers fed the diet supplemented with Salvia officinalis essential oil in our study. Faix et al (2007) found 46 The combined treatment of Salvia officinalis essential oil and sodium selenite caused significantly lower activity of SOD in blood erythrocytes compared to that of broilers fed a basal diet or supplemented with sodium selenite only. L i n et al (2000) reported that polyphenols proved to be effective superoxide radical scavengers.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, essential oils and extracts of many plants have been studied for their antioxidant activities (Faix et al 2007(Faix et al , 2009Hussain et al 2011). Salvia officinalis is a very popular aromatic plant well known for its wide range of medicinal effects.…”
mentioning
confidence: 99%